Writ on water : the sources and reach of film imagination - Warren, Charles, 1948-2021; Rothman, William; Schulze, Joshua (Albany, NY : State University of New York Press, 2022)
"A powerful and original statement on the nature of film and the intimate relation of "film imagination" to our lives as human beings in the world"--
1. Nashville, West of the West -- 2. Whim, God, and the screen : Jean-Luc Godard's Hail Mary -- 3. Earth and beyond : on WR : mysteries of the organism -- 4. Blonde Venus : experiment successful beyond all dreams -- 5. The path of art in Chronicle of a summer and Le joli mai -- 6. Fiction and nonfiction in Chantal Akerman's films -- 7. Surprise and pain, writing and film : on Ross McElwee's Time indefinite -- 8. Two women in L'avventura -- 9. The unknown piano teacher -- 10. Three immersions : Jean-Pierre and Luc Dardenne's Rosetta -- Postscript: The integrity of film.
Includes bibliographical references and index.
Description based on online resource; title from digital title page (viewed on April 01, 2022).
JSTOR
Keywords: Motion pictures -- Philosophy; Motion pictures -- History; Film criticism; Cinéma -- Histoire; Critique cinématographique.; Cinéma -- Philosophie; Film criticism; Motion pictures; Motion pictures -- Philosophy; History